2016
DOI: 10.1088/1742-6596/683/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Quantum spin liquid and electric quadrupolar states of single crystal Tb2+xTi2-xO7+y

Abstract: The hidden ordered state of the frustrated pyrochlore oxide Tb2+xTi2−xO7+y is possibly one of the two electric multipolar, or quadrupolar, states of the effective pseudospin-1/2 Hamiltonian derived from crystal-field ground state doublets of non-Kramers Tb 3+ ions. These long-range orders are antiparallel or parallel alignments of transverse pseudospin components representing electric quadrupole moments, which cannot be observed as magnetic Bragg reflections by neutron scattering. However pseudospin waves of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 24 publications
4
29
1
Order By: Relevance
“…While it is now suggested that Tb 2 Ti 2 O 7 crystals may be inhomogeneous [35], we find that the lattice strain of our Tb 2 Ti 2 O 7 crystal (and LD probes the bulk of a large crystal) is not generally larger than the other two compounds.…”
Section: Discussioncontrasting
confidence: 58%
“…While it is now suggested that Tb 2 Ti 2 O 7 crystals may be inhomogeneous [35], we find that the lattice strain of our Tb 2 Ti 2 O 7 crystal (and LD probes the bulk of a large crystal) is not generally larger than the other two compounds.…”
Section: Discussioncontrasting
confidence: 58%
“…The slight Q-dependence and the non-resolution limited peak-width, ∆E ≫ (∆E) resolution = 0.01 meV, have been one of the puzzling observations of TTO. The present interpretation using the composite spin-quadrupole wave can be an answer 23,24 .…”
Section: Magnetic Spectra Of Polycrystalline Tb2+xti2−xo7+ymentioning
confidence: 62%
“…1(a)], which suggests that the elusive spin-liquid state of TTO is the U(1) QSL. We emphasize that a high-quality single-crystalline sample with a well-controlled x value [35] enables us to accomplish this work.…”
mentioning
confidence: 99%
“…Polycrystalline and single-crystalline Tb 2+x Ti 2−x O 7+y samples were prepared by a standard solid-state reaction [34] and by a floating zone method [35]. Specific heat was measured by a quasi-adiabatic method down to 0.1 K using a plate-shape crystal with a size of 0.7 × 0.9 × 0.1 mm 3 whose shortest dimension is along a [110] axis.…”
mentioning
confidence: 99%
See 1 more Smart Citation